Development, Implementation, Evaluation, and Comparation Toward ELT Curriculum (A Case in Indonesia) - Leni Kicha; Tini Mogea; Nihta V. F. Liando (Edumaspul: Jurnal Pendidikan, 2023)
The study aims to shed light on the multifaceted landscape of English Language Teaching (ELT) curriculum in the context of its development, implementation, evaluation, and comparative analysis. The first phase of the study delves into the developmental aspect of ELT curriculum, examining the underlying theories, methodologies, and best practices that inform its construction. Through content analysis, and document review, the research seeks to uncover the pedagogical innovations, curricular adaptations, and the development of ELT curriculum. In the subsequent phase, the study investigates the practical implementation of ELT curriculum within the classroom environment. By employing classroom observations, content analysis, the research scrutinizes the translation of curriculum design into instructional practice, including the strategies used, the learning materials selected, and the student-centered approaches employed. The third phase of this study centers on the evaluation of ELT curriculum effectiveness. It utilizes assessment tools, outcome measurements, and student and teacher evaluations to gauge the impact of the curriculum on language proficiency, teaching effectiveness, and learning outcomes. Through a systematic review of different curriculum models, the study seeks to identify disparities, strengths, and weaknesses in diverse ELT approaches. This comparative perspective helps inform recommendations for potential improvements and adjustments in curriculum design and implementation. In summation, this qualitative study contributes to the ongoing discourse on ELT curriculum by unraveling its development, implementation, evaluation, and comparative aspects. By gaining a deeper understanding of the intricacies and variations within ELT curriculum, educators and policymakers can make informed decisions to enhance the quality of English language education.